CYP2E1 and miRNA‐378a‐3p contribute to acetaminophen‐ or tripterygium glycosides‐induced hepatotoxicity. Issue 2 (20th October 2019) - Chen, Keguang; Guo, Nan; Zhang, Rui; Wei, Chunmin; Guo, Ruichen
Abstract: Increased expression of CYP2E1 may represent the main factor contributing to oxidative stress‐mediated liver damage in drug‐induced liver injury (DILI). However, the regulation mechanism of CYP2E1 expression is poorly described. The present study was aimed to investigate the role of CYP2E1 in acetaminophen (APAP)‐ or tripterygium glycosides (TG)‐induced hepatotoxicity as well as the regulation of CYP2E1 and miR‐378a‐3p expression by APAP or TG. Rats were randomly divided and treated with APAP, TG, chlormethiazole (CMZ), APAP + CMZ and TG + CMZ, respectively, for 4 weeks. Then, blood and liver samples were collected. Serum and hepatic biochemical parameters were measured using commercial kits. Liver histopathology was tested by H&E staining. Expression levels of CYP2E1 mRNA and miR‐378a‐3p were detected by qRT‐PCR. CYP2E1 protein expression was determined by Western blot. Our results showed that CMZ effectively restored the hepatic histopathological changes, oxidative stress biomarkers and TNF‐α levels induced by APAP or TG. CYP2E1 mRNA and/or protein expression levels were dramatically increased after chronic APAP or TG treatment, while this induction was significantly reversed by CMZ co‐treatment. Of note, miR‐378a‐3p expression levels were significantly suppressed after APAP, TG and/or CMZ treatment. These results suggested that CYP2E1 were highly induced after chronic APAP or TG treatment, which in turn play an important role in APAP‐ or TG‐induced hepatotoxicity. These inductions of CYP2E1 expression were probably carried out by inhibition of miR‐378a‐3p. Our findings might provide a new molecular basis for DILI.